Current Concepts on the Pathogenesis of Peri-implantitis: A Narrative Review - Fragkioudakis, Ioannis; Tseleki, Georgia; Doufexi, Aikaterini-Elisavet; Sakellari, Dimitra (European Journal of Dentistry, 2021)
As implant treatment has been integrated in contemporary dental practice, complications with the forms of peri-implant mucositis and peri-implantitis have also increased in prevalence. Peri-implantitis is the more severe biological complication and is defined as an inflammatory disease affecting peri-implant tissues resulting in bone and eventually implant loss. In addition, the treatment of peri-implantitis has currently become a substantial global economic burden. In the current study, a search was conducted in several electronic databases using specific keywords relevant to the article’s main topic. An increasing number of scientific reports have investigated the etiopathology of peri-implant diseases, focusing mainly on peri-implantitis. Microbial biofilm consists an important etiological factor of peri-implant pathology analogous to periodontal diseases. Although several data confirm that peri-implant infections are dominated by gram-negative bacteria, similar to periodontal infections, there is evidence that some cases may harbor a distinct microbiota, including opportunistic microorganisms and/or uncultivable species. Additionally, data support that several parameters, such as genetic predisposition of individual patients, occlusal overload, and local factors such as titanium particles and excess cement, may be implicated in peri-implantitis pathogenesis. Simultaneously, the release of titanium metal particles and their biological consequences or the presence of excess cement in the adjacent peri-implant tissues have also been suggested as factors that contribute to peri-implant pathology. A specific line of research also indicates the role of foreign body response to implant installation. This narrative review aims to discuss the current concepts of etiopathogenetic factors implicated in peri-implantitis.
Keywords: peri-implantitis; foreign body; risk factors